The Predictive Performance of Depressive Symptoms in the Second Trimester of Gestation for Postnatal Depressive Symptoms in a Primary Care Setting - Kwong Ho Tam; In Wong (Mary Ann Liebert, 2021)
Purpose: The aim of this study was to determine and quantify the predictive performance of depressive symptoms in the second trimester for postnatal depressive symptoms and to raise awareness of psychosocial problems. Methods: This was a prospective longitudinal study. The experimental group comprised Chinese women who completed the Edinburgh Postnatal Depression Scale (EPDS) two times (once during the second trimester and once at 6?8 weeks postdelivery) at Fong Son Tong Health Center (CSSL), Macau. Descriptive statistics were used to analyze the collected data. The predictive performance was determined using paired t-tests and receiver operating characteristic curves. The control group was a pre-existing group that had only completed the EPDS at 6?8 weeks postdelivery. Finally, postnatal depressive symptoms (EPDS score ?12) were compared between the experimental and control groups. Results: In the experimental group, a total of 160 women completed the EPDS during the second trimester, and 137 (85.6%) completed the EPDS at 6?8 weeks postdelivery. The EPDS score in the second trimester was positively correlated with the score at 6?8 weeks postdelivery. The optimal threshold value of the EPDS score in the second trimester is ?7. Compared with the control group, there was statistical significance in the detection of postnatal depressive symptoms in the experimental group. Conclusions: Screening for possible depressive symptoms in the second trimester and actively following up with at-risk women in the postnatal period may be an effective strategy for improving postnatal mental health outcomes.